A new species of Lophiaris raf. (Orchidaceae) from the Pacific Coastal of Mexico - Balam Narváez, Ricardo (2013)
A species of Lophiaris Raf. (Orchidaceae: Cymbidieae: Oncidiinae), Lophiaris natalieae, from Jalisco, Mexico, is proposed as new. The new species is described, illustrated and compared to Lophiaris lurida, from which is different by its lateral sepals shortly connate at base, and its transversely narrower central labellum lobe. Its distribution and habitat are discussed. Conservation status of the new taxon is assessed against the MER criteria.